Rewrite the equation by completing the square X^2+6x+9=0 (X+?)^2=?

Question

Rewrite the equation by completing the square
X^2+6x+9=0
(X+?)^2=?

in progress 0
Serenity 1 month 2021-09-16T03:00:27+00:00 2 Answers 0

Answers ( )

    0
    2021-09-16T03:01:43+00:00

    Answer:

    x^2 + 6x  +9 = 0

    (x+3)^2 = 0

    (x+3)(x+3)= 0

    Step-by-step explanation:

    0
    2021-09-16T03:01:58+00:00

    Answer:(x+3)^2

    Step-by-step explanation: I have done it on khan academy

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )